Adsorption of oil from aqueous solution onto environmental friendly microsorbent / Nurul Izza Husin, Vicinisvarri Inderan and Ainnie Rahayu Abdullah - Husin, Nurul Izza; Inderan, Vicinisvarri; Abdullah, Ainnie Rahayu (2011)
Over the recent years there has been an increasing concern for environmental risk of industrial activities associated with extraction, hydrocarbons, food processing, transportations and refining. These industries have increased the threat of oil pollution to the environment and subsequently concomitant discharged into the natural environment creates major ecological problem throughout the world. The wastewater is detrimental and need to have a treatment before discharge into the environment, in line with Malaysian Environmental Quality Act 1974. Removal of oil from wastewater can be achieved by several techniques, such as precipitation, flocculation, adsorption, ion exchange, etc. Among the available methods, adsorption using activated carbons has been shown to be one of the most ideal procedures. However, there are a number of problems associated with activated carbons such as combustion at high temperature, pore blocking, and hygroscopicity.To overcome the problems associated with activated carbons is using alternative adsorbents. The alternative adsorbents could be generated from agriculture waste. These materials are available in large quantities and may have potential as adsorbents due to their physico-chemical characteristics. In the present study, the ability of banana pseudostem fibers and durian shell as a biosorbent for the removal of oil from synthetic oily wastewater was investigated. A detailed batch study with respect to its adsorption equilibrium, isotherm and kinetics were carried out at ambient temperature, various initial concentration of oil and agitation time. The batch study clearly shows that banana pseudostem and durian shell exhibit almost 100% adsorption at lower concentration of oil. Langmuir and Freundlich adsorption model were applied to describe the experimental isotherm and isotherm constants. Equilibrium data fitted well with Freundlich model. The kinetic data were best fitted to pseudo-second-order kinetic model. The result showed that these low-cost adsorbent had a high adsorption capacity, making it suitable for the oily wastewater treatment.